Discovery and refinement of genetic loci associated with cardiometabolic risk using dense imputation maps - Iotchkova, V; Huang, J; Morris, J; Jain, D; Barbieri, C; Walter, K; Min, J; Chen, L; Astle, W; Cocca, M; Deelen, P; Elding, H; et al. (Nature Publishing Group, 2016)
Large-scale whole genome sequence datasets offer novel opportunities to identify genetic variation underlying human traits. Here we apply genotype imputation based on whole genome sequence data from the UK10K and the 1000 Genomes Projects into 35,981 study participants of European ancestry, followed by association analysis with twenty quantitative cardiometabolic and hematologic traits. We describe 17 novel associations, including six rare (minor allele frequency [MAF]<1%) or low frequency variants (1%<maf<5%) (hdl)="" (mch,="" (plt),="" 20="" 233="" 59="" additional="" allelic="" analysis="" and="" applying="" architecture="" associated="" associations="" augment="" biological="" cardiometabolic="" cell="" cholesterol.="" count="" credible="" describe="" diseases,="" enrichments="" factors="" findings="" fine-mapping="" for="" function.="" functional="" hematologic="" high-density="" identification="" indices="" insights="" known="" less="" lipoprotein="" loci="" mcv)="" novel="" of="" or="" p="" platelet="" potentially="" predicted="" provide="" red="" regions="" regulatory="" resolve="" risk="" sets="" targets.<="" the="" these="" to="" trait="" traits,="" twenty="" understanding="" variants,="" we="" with="" within=""></maf<5%)>